2008
DOI: 10.2174/1874095200801020052
|View full text |Cite
|
Sign up to set email alerts
|

Hydroamination of Terminal Alkynes by Amines Catalyzed by Copper Heteropoly Salts: A Simple Approach Towards Imine Synthesis

Abstract: Abstract:The hydroamination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. Heterogeneous intermolecular hydroamination reactions of alkynes with aromatic amines using different inexpensive copper salts of hetropolyacid catalysts were investigated. Among heteropoly salts, copper salts of silicotungstic acid showed highest activity. Reactivity of aromatic amines increased with increase in its basicity. Acidity in heterogeneous cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…Intermolecular Hydroamination: The substrates were purchased from Aldrich, AlfaAesar and Acros. The 1 H NMR spectra of N ‐(methylbenzylidene)aniline,40 N ‐(1‐phenylethylidene)‐2,4,6‐trimethylaniline,41 and N ‐[1‐(cyclohex‐1‐en‐1‐yl)ethylidene]‐2,4,6‐trimethylaniline are in agreement with the previously reported data 42…”
Section: Methodssupporting
confidence: 91%
“…Intermolecular Hydroamination: The substrates were purchased from Aldrich, AlfaAesar and Acros. The 1 H NMR spectra of N ‐(methylbenzylidene)aniline,40 N ‐(1‐phenylethylidene)‐2,4,6‐trimethylaniline,41 and N ‐[1‐(cyclohex‐1‐en‐1‐yl)ethylidene]‐2,4,6‐trimethylaniline are in agreement with the previously reported data 42…”
Section: Methodssupporting
confidence: 91%
“…63 Hydroamination describes the addition of an N-H bond of an amine to an alkene or alkyne in one step with subsequent formation of nitrogen containing compounds. 72 In the catalytic studies the activity of dizincocene 1 was compared with previously published catalysts [73][74][75][76][77][78][79] by using the standard reaction, the addition of 2,4,6-trimethylaniline to phenylethyne (Scheme 19). These studies clearly showed the high potential of 1 for this type of reaction.…”
Section: Catalytic Applications Of Low-valent Organozinc Complexesmentioning
confidence: 99%
“…As test reaction we used the addition of 2,4,6-trimethylaniline to phenylethyne because this reaction has also been studied with many other reported catalysts (Table ). , Most reported catalysts for this reaction shown in Table are based on group 11 metals, although there are some exceptions such as a titanium catalyst (Table , entry 5). All three zinc catalysts ( 1 – 3 ) (Table , entries 1–3) catalyze the transformation at room temperature, whereas most of the other systems operate in the range 90–110 °C (Table , entries 4–9 and 11–13).…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectra of N -(methylbenzylidene)aniline, methylphenyl(1-phenylvinyl)amine, N -(1-phenylethylidene)-4-chloroaniline, N -(1-phenylethylidene)-2,4,6-trimethylaniline, N -[1-(4-bromophenyl)ethylidene)]benzamine, N,N -dimethyl-4-[1-(phenylimino)]ethylaniline, N -[1-(1-cyclohexene-1-yl)ethylidene]benzamine, N -(1-methylheptylidene)benzamine, 4-chlor- N -(1-methylheptylidene)benzamine, and N -(1-phenylethylidene)benzmethanamine conform to the literature.…”
Section: Methodsmentioning
confidence: 99%